Thinking through new literacies for primary and early years - Metcalfe, Jayne; Todd, Ian; Simpson, Debbie; Toyn, Mike (Los Angeles, Calif. SAGE/Learning Matters, 2013)
This accessible book challenges readers to reconsider what is meant by the term 'literacy'. It encourages a deep consideration of literacy in the post-typographic age. Written for education students, it draws on current research and makes links between the theory and practice. It explores some technological innovations designed to support the emergent reader and writer and covers aural and oral literacies, visual literacies and the legal and ethical issues arising from this new era. Readers are helped to think through 'new literacies' and their place in primary schools. Throughout, critical thinking exercises help the reader develop their own analytical skills.
Includes bibliographical references and index
Keywords: Literacy -- Study and teaching (Elementary) -- Great Britain